Cytotoxicity and cytoprotective effects of citrus flavonoids on insulin-secreting cells BRIN-BD11: beneficial synergic effects. - Felipe, E.; Maestri, J.; Kanunfre, C.; Curi, R.; Newsholme, Philip; Carpinelli, A.; Oliveira-Emilio, H. (Taylor & Francis, 2013)
Flavonoids, in general, have potent antioxidant activity and they can be used in treating chronic diseases involving oxidative stress, such as diabetes mellitus. The purpose of this study was to evaluate the cytotoxicity and cytoprotective effects of citrus flavonoids on the functionality of BRIN-BD11 cells. The assessment of cytotoxic and cytoprotective flavonoid tested was performed using the MTT reduction assay. The flavonoids did not show cytotoxic effects in any of the tested concentrations (5–20 mM) and also negative insulinotropic effects were not observed. To cytoprotective assay, the IC50 of H2O2 in treatment of 2 h (acute oxidative stress) was measured (350 mM). Moreover, under acute oxidative stress, the isolated flavonoids (10 mM) had no cytoprotective effects. Besides an antioxidant role of the flavonoids was only observed when using in association. Thus future experiments are needed, varying the experimental condition, to better evaluate the possible mechanisms of action of these flavonoids.